(untitled) (Nigerian Journal of Technology, 2015)
In this study, the treatment of the effluents of an artisanal tannery by electrocoagulation with iron electrodes was carried out. During electrolytic treatment, a current intensity of 0.4 A was used, and the electrolysis time was varied from 0 to 40 minutes. The performance of electrocoagulation was compared with that of chemical coagulation with ferric sulfate. The results obtained showed that highest removals after electrocoagulation were 71.15, 98.26, and 86.59% for the COD, colour and turbidity respectively. Chemical coagulation reduced the COD up to 83.17%, while colour and turbidity removals were 99.81 and 98.62% respectively. Although chemical coagulation leads to highest percentage removals after treatment, electrocoagulation results in near neutral pH values and also decrease conductivity weakly. By contrast, chemical coagulation increases the acidity of the effluent and its conductivity. Hence with close to neutral pH and weak conductivity values obtained for effluents treated by electrocoagulation, it is inferred that such treated effluents can be recycled. http://dx.doi.org/10.4314/njt.v35i1.29